2020
DOI: 10.2139/ssrn.3753742
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Covid-19 on Productivity

Abstract: views do not necessarily represent those of the Bank of England or its Committees. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…However, repercussions of lockdowns such as self-quarantine and social distancing, strictly reduce productivity and efficiency at work. Lockdowns and work disruptions also cause myriads of adverse health impacts (Kitagawa et al, 2021), and distract the senior management from their productivity in dealing with the pandemic (Bloom et al, 2020). Lack of labour supervision during lockdowns is seen as the main underpinning factor influencing labour productivity and efficiency (Quezon et al, 2021).…”
Section: Diminution In Productivity and Efficiency (Dp)mentioning
confidence: 99%
“…However, repercussions of lockdowns such as self-quarantine and social distancing, strictly reduce productivity and efficiency at work. Lockdowns and work disruptions also cause myriads of adverse health impacts (Kitagawa et al, 2021), and distract the senior management from their productivity in dealing with the pandemic (Bloom et al, 2020). Lack of labour supervision during lockdowns is seen as the main underpinning factor influencing labour productivity and efficiency (Quezon et al, 2021).…”
Section: Diminution In Productivity and Efficiency (Dp)mentioning
confidence: 99%
“…Demand for goods and services in many sectors declined. Bloom et al. (2020) find a significant decline in the productivity of private firms in the fourth quarter of 2020 in the United Kingdom due to the measures used to contain Covid-19.…”
Section: Introductionmentioning
confidence: 96%
“…The second strand of literature has documented the effects of Covid-19 on firms. Several descriptive studies have shown that firms experienced severe distress in both developed ( Bloom, Bunn, Mizen, Smietanka, Thwaites, 2020 , Bloom, Fletcher, Yeh, 2021 , Torrès, Benzari, Fisch, Mukerjee, Swalhi, Thurik, 2022 ) and developing countries ( Shen, Fu, Pan, Yu, Chen, 2020 , Nair, 2021 , Nordhagen, Igbeka, Rowlands, Shine, Heneghan, Tench, 2021 ). Besides examining firms’ outcomes in the post-lockdown period, we also explore the impact in a recovery phase two quarters after the lockdown ended and find that firms recovered in this later phase.…”
Section: Introductionmentioning
confidence: 99%
“…Having said the above, it is reasonable to anticipate that the severity of the damage across industries has been driven by their vulnerability and capacity to cope with the new business environment. Given these asymmetries, reconsidering their business models and strategies has emerged as a priority for many players aiming to meet customer needs and secure their existence in light of the global market reshape caused by COVID-19 (Barrero et al 2020;Bloom et al 2020;Deloitte 2020;Denger 2020). Accordingly, the impact of the recent pandemic on particular sectors still remains a black box, despite a variety of expectations.…”
Section: Introductionmentioning
confidence: 99%